Intercellular Signalling in the Mammary Gland 1995
DOI: 10.1007/978-1-4615-1973-7_50
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Triiodothyronine Administration on the Disposal of Oral [1-14C]-Triolein, Lipoprotein Lipase Activity and Lipogenesis in the Rat during Lactation and on Removal of the Litter

Abstract: The effect of tri-iodothyronine (T3) administration on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Thyroid hormones affect a number of physiological processes including lipid, carbohydrate, and protein metabolism (8)(9)(10). Studies with litter-removed lactating rats have shown that hyperthyroidism depresses lipoprotein lipase (LPL) activity in mammary gland and white adipose tissue (7).…”
mentioning
confidence: 99%
“…Thyroid hormones affect a number of physiological processes including lipid, carbohydrate, and protein metabolism (8)(9)(10). Studies with litter-removed lactating rats have shown that hyperthyroidism depresses lipoprotein lipase (LPL) activity in mammary gland and white adipose tissue (7).…”
mentioning
confidence: 99%